Disaster risk reduction policies and perceived community resilience in rural ethnic minority communities in China - Zhihan Dai; Guochun Wu (Humanities & Social Sciences Communications)
Abstract Ethnic minorities are particularly vulnerable to disasters, yet limited studies have compared the effectiveness of disaster risk reduction (DRR) among these communities in China. This paper aims to fill that gap by utilizing face-to-face survey data collected from six counties, which include Yi, Tibetan, Tajik, and Uyghur ethnic communities in Sichuan Province and Xinjiang Uyghur Autonomous Region. These counties are located in earthquake-prone areas. The survey employed a modified version of the Community Advancing Resilience Toolkit (CART) to assess disaster preparedness and the factors influencing it within these ethnic communities. The results revealed variations in resilience among the different ethnic groups. Factors that affect perceived community resilience include not only individual characteristics but also aspects of policy. The study identified inter-provincial differences in perceived community resilience and emphasized the need for policies that address these disparities.